METHODOLOGICAL NOTES ON THE METAPHYSICAL IMPRESSIONS (SUMMING UP THE RESULTS OF THE CONFERENCE) - Ludmila B. Logunova; Yuriy Yu. Petrunin (Высшее образование в России)
The review presents the main topics of the reports on the first all-Russian scientific-practical conference "Philosophy of creation", which has become a landmark event in the life of Russian philosophical community. The paper focuses on the basic areas in the study ofcreativity that are defined by the various methodological approaches, defines their heuristic effectiveness. The authors have analyzed the trend of creating transdisciplinary methodology, combining achievements of natural science, modern neuroscience and the humanities in the study of creativity, its capacity and status in contemporary epistemology.